1997
DOI: 10.1007/s002239900258
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Spinal Degenerative Changes on the Evaluation of Bone Mineral Density with Dual Energy X-Ray Absorptiometry (DXA)

Abstract: The purpose of this study is to evaluate degenerative factors in a postmenopausal patient group and differentiate the influence on bone mineral density (BMD) measurements by dual-energy X-ray absorptiometry (DXA). The patients and methods included an investigation of 144 postmenopausal women (mean 63.3 years) with PA-DXA of the spine. Degenerative factors (osteophytes, osteochondrosis, scoliosis, and vascular calcification) were evaluated from plain lumbar radiographs, their estimated probability was analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
1
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(94 citation statements)
references
References 17 publications
3
83
1
1
Order By: Relevance
“…It has been long understood that spinal BMD measurements in older people using DXA technology, are subject to variation due to both difficulties in interpreting images, and inherent additional bone mineral being present where the spine may be degenerate, have calcification of the aorta projected over it or anatomical variation with scoliosis in addition to other normal variants such as absent or additional vertebrae [15].…”
Section: Discussionmentioning
confidence: 99%
“…It has been long understood that spinal BMD measurements in older people using DXA technology, are subject to variation due to both difficulties in interpreting images, and inherent additional bone mineral being present where the spine may be degenerate, have calcification of the aorta projected over it or anatomical variation with scoliosis in addition to other normal variants such as absent or additional vertebrae [15].…”
Section: Discussionmentioning
confidence: 99%
“…6,8,[14][15][16] Studies analyzing the intensity of osteophytes have shown that the greater the intensity of this abnormality, the higher the increase in bone mineral density is. 3 It is clear that osteophytes can lead to an apparent increase in bone mineral density, although it is not clear whether this increase is associated with a decrease in fractures.…”
Section: Discussionmentioning
confidence: 99%
“…6 Degenerative factors such as, osteophytes, osteochondrosis, scoliosis and vascular calcification are increased from 35% to 80% in the 55 to 70 years age group. 7 It has been accepted generally that conditions of osteoporosis and osteoarthritis are different diseases, possibly resulting from different pathomechanisms. Several investigators have examined the coexistence of osteoporosis and spondylosis in the spine and have reported an inverse relation between decreased bone mineral density (BMD) and intervertebral disc degeneration.…”
Section: Methodsmentioning
confidence: 99%